An improvement of the method for assessing the efficiency of the methods of performing tasks by the naval forces in the conditions of hybrid operations - Vdovytskyi, Yevhenii; Yakymiak, Stepan (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the research is the use of forces (troops) of the Naval Forces (Navy). The subject of the research is the process of evaluating the effectiveness of the use of Navy in various ways. An improved method for assessing the effectiveness of the ways of performing tasks by the forces (troops) of the Navy during the performance of the tasks of protecting the economic activity of the state at sea in the conditions of the enemy’s hybrid actions is proposed. The method has the following sequence of actions: ‒ an input of initial data; ‒ calculation of the probability of a timely response to enemy actions; ‒ calculation of the probability of the enemy’s refusal to act; ‒ calculation of the probability of ensuring the protection of objects conducting economic activity of the state at sea; ‒ calculation of the mathematical expectation of the number of objects that conduct economic activity at sea and will be protected by the Naval forces (troops); ‒ calculation of the protection degree of objects conducting economic activity at sea; ‒ calculation of the degree of decrease in the carrying capacity of ships (for tasks related to sea transportation); ‒ calculation of the mathematical expectation of the avoided loss of economic activity; ‒ determination of the protection degree of economic activity; ‒ determination of costs of material and technical resources; ‒ choosing the best (rational) way of using the Naval forces (troops) in accordance with the chosen criterion. The novelty of the method consists in the use of an improved system of indicators for evaluating the effectiveness of the Navy’s methods of performing tasks, taking into account the dependence of the amount of mediated damage caused by sea transportation on the actions of the enemy and taking into account the effect of the Navy’s demonstration actions and the use of simulation tools on the effectiveness of task performance. The considered example showed a 25–40 % increase in assessment accuracy due to the consideration of additional conditions and factors